Rebuilding our community networks post-COVID-19: Perspectives from the University of St Andrews Open Access team - Brady, Kyle; Knowles, Kirsty (Septentrio Conference Series, 2022)
Background. Communities of Practice (CoP) have long been discussed for their abilities to support individuals in decision making, knowledge sharing, and collegiate support[1]. Individuals who are actively involved in CoP can also act as agents for change within an institution[2]. The University of St Andrews Open Access team have developed strong links to School administrators and established ‘deposit hubs’ in Schools whereby researchers can get local support from the ‘hubbers' for creating new research output records in the University’s Current Research Information System (CRIS), as well as support for uploading open access versions and input based on specialist local knowledge such as linking research grants. Aims. To assess the impact of COVID-19 on the CRIS activity of our ‘hubbers’, to determine whether more could be done to improve resilience in the face of time-constraining factors. We also sought to determine what measures might be taken to improve communication channel within the University and how a network might develop and grow. Methods. A quantitative assessment of the impact of COVID on the CRIS activity of hubbers and administrators whom we have developed links with. Through qualitative assessment and dialogue with administrators we wanted to ascertain other issues that result in delays or non-deposit. Results. There was a correlation between the uptick in CRIS record creation and manuscript deposit activity by the Open Access team, and a decrease in activity by ‘hubbers'. Feedback received also suggested there was inertia due to common queries arising, and further inactivity due to inadequacies with communication channels. It was also clear that the uptick in administrative effort from the OA team needed to be addressed. Conclusion. Determining a correlative effect of a discrete set of administrative tasks based on quantitative indicators is prone to error. However, the Open Access team is confident that such Communities of Practice do add value to research culture, both in quantitative measurable results, and in terms of qualitative cultural effects. But more is needed to be done to enhance resilience, transparency, and confidence. It was decided therefore that a frictionless communication channel was required using Microsoft Teams, to bring together ‘hubbers’ and limit wasted effort by sharing best practice, a set of resources, and guides to ensure common standards and consistency, as well as an FAQ section.